2022
DOI: 10.3389/fenvs.2022.993333
|View full text |Cite
|
Sign up to set email alerts
|

Differential characteristics and driving forces of the spatial distribution of heritage trees in Luoyang, an ancient capital of China

Abstract: Heritage trees have important historical, landscape, and ecological value. Exploring the spatial distribution pattern of heritage trees is of great importance to the construction of ecological civilization and the connotation of regional history and culture. This paper took 5,216 heritage trees in Luoyang, an ancient capital of China, as the research object and used geospatial analysis methods and a geographically weighted regression model to analyze the differences and driving forces of the spatial distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Some 96.99% of the trees resided in the countryside, and the tree density was 0.10 trees/km 2 , which is very close to the nationwide statistical result of 95.15% and 0.13 trees/km 2 , respectively [7,37]. Similar to previous studies [14,20,66], the distribution of scattered large old trees showed an agglomerative pattern, with several clusters in Yi County, Laiyuan, and Quyang. A greater tree number was found in habitats of village fringe (VF), government/community/institutional ground (GC), and scenic resort/historic site (SRHS).…”
Section: Rural Large Old Tree Protection Is Faced With More Challengessupporting
confidence: 86%
See 4 more Smart Citations
“…Some 96.99% of the trees resided in the countryside, and the tree density was 0.10 trees/km 2 , which is very close to the nationwide statistical result of 95.15% and 0.13 trees/km 2 , respectively [7,37]. Similar to previous studies [14,20,66], the distribution of scattered large old trees showed an agglomerative pattern, with several clusters in Yi County, Laiyuan, and Quyang. A greater tree number was found in habitats of village fringe (VF), government/community/institutional ground (GC), and scenic resort/historic site (SRHS).…”
Section: Rural Large Old Tree Protection Is Faced With More Challengessupporting
confidence: 86%
“…The nearest neighbor index (R) is defined as the ratio of the actual nearest neighbor distance to the theoretical nearest neighbor distance [14]. Here, it was used to discover the distribution patterns (including random, uniform, or cohesive) of scattered large old trees in Baoding City and Xiongan New Area.…”
Section: Statistical and Spatial Analysis Of The Scattered Large Old ...mentioning
confidence: 99%
See 3 more Smart Citations